Pengetahuan, Sikap, dan Perilaku Mahasiswa Keperawatan dalam Menangani Kejadian Ikutan Pasca Imunisasi (KIPI) Vaksin Covid-19 - Koelima, Bellandina Susana Junianty; Damayanti, Catharina Rossa; Baky, Jermias Helrari; Gultom, Eva Chris Veronica; Aiba, Sumiaty (Jurnal Kesehatan Holistic, 2023)
Introduction: Post-immunization follow-up events (KIPI) for COVID-19 vaccine are medical symptoms that are suspected to be related to the COVID-19 vaccine, either in the form of vaccine reactions, injection reactions, pharmacological effects, or procedural errors. Good knowledge about AEFI can influence people's attitudes and behavior in dealing with follow-up events after COVID-19 immunization. The results of a brief survey obtained data from 35 respondents with 17 respondents (47.8%) not knowing what AEFIs were and as many as 18 respondents (51.4%) knowing what AEFIs were and how to handle them. Objective: The purpose of this study was to describe the knowledge, attitudes, and behavior of nursing students in handling the COVID-19 vaccine AEFI. Methods: The method used in this research is descriptive quantitative with a total sampling of 100 people. The instrument in this study used a questionnaire with univariate analysis techniques. Result: The results showed that 80% of respondents had good knowledge about handling COVID-19 vaccine AEFIs, 75% of respondents who had a good attitude, and 79% of respondents who had good behavior. Knowledge, attitudes, and behavior of respondents are included in the good category because they are influenced by educational, environmental, socio-cultural factors, personal experience, mass media, educational institutions, and other people who are considered important. Conclucion: Further research can investigate further regarding the handling of the COVID-19 vaccine AEFI by using a qualitative descriptive method.